The Impact of Bullying in the Perspective of Positive Law: A Case Study of Handling and Prevention in the Campus Environment - Asmariah, Asmariah (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Bullying is a significant problem that can occur in various environments, including among students. This study aims to conduct an in-depth exploration of how positive law regulates and deals with bullying crimes in the campus environment of Universitas Faletehan. The findings show that victims of bullying at the university often experience negative impacts such as stress, anxiety, and depression. The results from the study highlight the specific challenges faced by campus security or relevant authorities in enforcing the law against bullying cases, which directly affect the implementation of justice. In addition, the findings highlight the need for a more sensitive and responsive approach to the psychological needs of victims, as well as increased knowledge and support for mental health in the university environment. These findings emphasize the need to develop more comprehensive and proactive policies in addressing bullying, including more effective reporting mechanisms, collaboration with online platforms to remove harmful content, and better victim support programs.